2017
DOI: 10.1038/srep41669
|View full text |Cite
|
Sign up to set email alerts
|

The PRC2-binding long non-coding RNAs in human and mouse genomes are associated with predictive sequence features

Abstract: Recently, long non-coding RNAs (lncRNAs) have emerged as an important class of molecules involved in many cellular processes. One of their primary functions is to shape epigenetic landscape through interactions with chromatin modifying proteins. However, mechanisms contributing to the specificity of such interactions remain poorly understood. Here we took the human and mouse lncRNAs that were experimentally determined to have physical interactions with Polycomb repressive complex 2 (PRC2), and systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…S15 C and D). Recent studies have revealed that PRC2-binding lncRNAs have distinctive and evolutionarily conserved sequence features across species (63). Thus, we analyzed the binding capacity of AK021986 and PRC2 using the lncPro calculation method (64).…”
Section: Discussionmentioning
confidence: 99%
“…S15 C and D). Recent studies have revealed that PRC2-binding lncRNAs have distinctive and evolutionarily conserved sequence features across species (63). Thus, we analyzed the binding capacity of AK021986 and PRC2 using the lncPro calculation method (64).…”
Section: Discussionmentioning
confidence: 99%
“… 134 The general properties, if they exist, through which these lncRNAs couple PRC2 to chromatin are the focus of continued investigation. 135 , 136 It may be that the genes for these molecules are distributed across the genome and the lncRNAs in turn all act in a local manner to recruit and modulate chromatin machinery to a given gene expression environment. 137 Yet there are clear limitations were the cell to attempt to repeat this process with other lncRNAs: physiological transcriptional profiles in adult cells do not involve turning on or off entire chromosomes, with genes temporally coregulated often residing on different chromosomes (each of which, in this model, would require its own lncRNA, although 3-dimensional chromatin environments may allow transcription factories to form bringing multiple mRNA-coding genes into a neighborhood governed by a single lncRNA) and beset by numerous histone modifications.…”
Section: Role Of Noncoding Rnas In Chromatin Function and Cardiovascumentioning
confidence: 99%
“…Support for this comes from a rich supply of literature indicating lncRNAs are invloved in establishing hetertochromatin in imprinting, X-chromosome inactivation, and RNAi-mediated heterochromatin. Thus it seems reasonable to speculate the rhythm in TERRA is directly involved in mediating rhythms in telomere heterochromatin [45, 47, 48]. However, there remains a significant amount research to understand the mechanism and timing of this model.…”
Section: Discussionmentioning
confidence: 99%